A nano-enzyme self-healing hydrogel with catalytic oxygen supply performance and a preparation method and application thereof
Patent Information
- Application Number
- CN202410109949.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-25
AI Technical Summary
然而,大部分纳米酶生物学功能单一,例如缺乏诱导血管生成和调控组织再生动态过程的生物学活性
[0020]本发明中首先利用具有抗氧化和促血管化等生物活性的多酚类化合物丹酚酸B为配体合成丹酚酸B铜纳米团簇,基于丹酚酸B的酚羟基和铜形成铜配位结构,这种铜配位结构形成了类似天然氧化还原酶的催化活性中心,赋予铜团簇优异的类超氧化物歧化酶和类过氧化氢酶的级联催化活性。在铜团簇的类超氧化物歧化酶活性的作用下将超氧阴离子自由基歧化生成过氧化氢和氧气;随后基于丹酚酸B铜纳米团簇的类过氧化氢酶活性将过氧化氢分解为氧气和水,这种供氧方式能够在组织损伤部位将多余的活性氧转化为溶解氧,同时维持稳定的过氧化氢来源确保原位持续性催化供氧,避免了传统依赖气态氧的输氧方式穿透深度有限的问题。本发明中纳米酶自愈合水凝胶的组分均为天然活性物质或体内微量元素,具有高生物安全性,并且其制备方法简单易行,反应条件温和,无需复杂的仪器设备。
Smart Images

Figure CN117919490B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanobiomaterials technology, and relates to a nanoenzyme self-healing hydrogel with catalytic oxygen supply properties, its preparation method, and its application. Background Technology
[0002] Oxygen, as an important signaling molecule and metabolic product, plays a crucial role in numerous physiological processes in the body. Hypoxia typically activates related intracellular signaling pathways, inducing oxidative stress and inflammation, affecting angiogenesis, and consequently leading to cellular dysfunction. This further exacerbates tissue damage or functional disorders such as kidney injury, lung injury, cardiovascular disease, and chronic wounds. For example, vascular damage and microcirculatory abnormalities caused by diabetic microvascular complications result in severe hypoxia at the site of diabetic chronic wounds, making them highly susceptible to local necrosis, persistent inflammation, and severe infection. This has become a leading cause of non-traumatic amputation worldwide. Therefore, improving oxygen supply and promoting vascularization are highly effective treatments for diabetic chronic wounds with poor blood supply and severe hypoxia at the lesion site.
[0003] To alleviate the severe hypoxic microenvironment at the site of chronic diabetic wounds and thus promote wound healing, researchers have been dedicated to developing effective systemic or local oxygen delivery strategies. Local oxygen delivery strategies such as Oxyband™ and Oxyenesys™ are widely used internationally. However, these oxygen delivery materials have short durations of action and limited tissue penetration. Furthermore, oxygen transport carriers such as hemoglobin and perfluorocarbon also suffer from low continuous oxygen delivery efficiency and biosafety concerns. Since host blood is the primary source of oxygen and nutrients, effectively constructing a healthy vascular network helps alleviate local hypoxia, promotes continuous oxygen delivery, and facilitates wound repair. In addition, effectively regulating the pathological microenvironment of the wound, such as reducing oxidative stress, plays a crucial role in chronic wound repair. Therefore, there is an urgent need to develop an oxygen delivery dressing that can efficiently and continuously deliver oxygen while alleviating oxidative stress and promoting vascularization to accelerate chronic wound healing.
[0004] The in-situ oxygen production from hydrogen peroxide via enzymatic catalysis is currently a hot research topic in local oxygen production. However, excessive hydrogen peroxide can easily irritate and damage wound sites, and catalase exhibits poor stability and activity in complex wound environments, thus limiting the further application of such novel dressings. Nanozymes, due to their advantages of low cost, high stability, ease of large-scale preparation, and surface modification, are expected to become a substitute for natural enzymes and have been widely studied. In particular, nanomaterials with both superoxide dismutase-like and catalase-like catalytic activities can continuously produce oxygen through nanozyme cascade reactions, thereby alleviating hypoxia and promoting tissue repair. However, most nanozymes have limited biological functions, such as lacking the biological activity to induce angiogenesis and regulate the dynamic processes of tissue regeneration. Therefore, it is necessary to develop a novel nanozyme wound repair dressing that combines efficient in-situ oxygen supply, oxidative stress reduction, and pro-angiogenic functions. Summary of the Invention
[0005] To address the shortcomings of existing technologies in efficiently supplying oxygen and promoting wound repair, and specifically targeting the hypoxic and poorly vascularized microenvironment of diabetic wounds, this invention aims to provide a nanoenzyme self-healing hydrogel with catalytic oxygen supply properties, its preparation method, and its applications. This preparation method utilizes the polyphenolic compound salvianolic acid B, which possesses antioxidant and angiogenic activities, as a ligand to synthesize copper cluster nanoenzymes, which are then loaded onto a self-healing hydrogel based on natural polymers. The resulting nanoenzyme self-healing hydrogel exhibits highly efficient enzyme-like in-situ catalytic oxygen supply and angiogenesis induction properties. The preparation method of the nanoenzyme self-healing hydrogel in this invention is simple and easy to implement, with mild reaction conditions and no need for complex equipment. The prepared nanoenzyme hydrogel possesses excellent superoxide dismutase-like and catalase-like activities, effectively scavenging endogenous reactive oxygen species and maintaining a stable source of hydrogen peroxide to ensure continuous in-situ catalytic oxygen supply. It also has the function of regulating vascular endothelial cells to promote angiogenesis, showing great application potential in the repair of tissue defects caused by hypoxia and vascular damage in chronic diabetic wounds.
[0006] To achieve the above objectives, the technical solution adopted in this application is as follows:
[0007] A method for preparing a nanoenzyme self-healing hydrogel with catalytic oxygen supply properties includes the following steps:
[0008] 1) Using ascorbic acid as the main reducing agent and salvianolic acid B as the surface ligand and co-reducing agent, copper cluster nanozyme of salvianolic acid B was prepared by reducing copper sulfate solution in aqueous phase in one step.
[0009] 2) Copper cluster nanozymes of salvianolic acid B were loaded into a self-healing hydrogel co-crosslinked with carboxymethyl chitosan, aldehyde-modified chondroitin sulfate and catalase to obtain a nanozyme self-healing hydrogel with catalytic oxygen supply properties.
[0010] Further, step 1) specifically involves mixing copper sulfate solution and salvianolic acid B solution, stirring until homogeneous, adding ascorbic acid, and reacting under heating to obtain salvianolic acid B copper nanoclusters.
[0011] Furthermore, the heating temperature is 40-50℃, and the time is 6-24 hours.
[0012] Furthermore, the ratio of salvianolic acid B, ascorbic acid to copper sulfate is 1-5 μmol: 100 μmol: 10 μmol.
[0013] Furthermore, in step 2), the amino group of carboxymethyl chitosan or the amino group of catalase reacts with the aldehyde group of aldehyde-modified chondroitin sulfate in a Schiff base reaction to form a self-healing hydrogel.
[0014] Further, the specific process of step 2) is as follows: the copper cluster nanozyme of salvianolic acid B is dispersed in an aldehyde-modified chondroitin sulfate solution, and then mixed with carboxymethyl chitosan solution and catalase solution to form a nanozyme self-healing hydrogel with catalytic oxygen supply properties.
[0015] Furthermore, the mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase is 2.5-5:5:0-0.25.
[0016] Furthermore, the loading of the copper cluster nanozyme of salvianolic acid B in the nanozyme self-healing hydrogel with catalytic oxygen supply properties was 1-8 mg / mL.
[0017] A nanoenzyme self-healing hydrogel with catalytic oxygen supply properties prepared according to the method described above.
[0018] Application of a nanoenzyme self-healing hydrogel with catalytic oxygen supply properties prepared according to the method in the repair of diabetic wounds.
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] This invention first utilizes salvianolic acid B, a polyphenolic compound with antioxidant and angiogenic activities, as a ligand to synthesize salvianolic acid B copper nanoclusters. Based on the phenolic hydroxyl group of salvianolic acid B and the copper forming a copper coordination structure, this copper coordination structure creates a catalytic active center similar to natural redox enzymes, endowing the copper clusters with excellent superoxide dismutase-like and catalase-like cascade catalytic activities. Under the action of the superoxide dismutase-like activity of the copper clusters, superoxide anion free radicals are dismutated to generate hydrogen peroxide and oxygen. Subsequently, based on the catalase-like activity of the salvianolic acid B copper nanoclusters, hydrogen peroxide is decomposed into oxygen and water. This oxygen supply method can convert excess reactive oxygen species into dissolved oxygen at the site of tissue damage, while maintaining a stable source of hydrogen peroxide to ensure continuous in-situ catalytic oxygen supply, avoiding the limited penetration depth problem of traditional oxygen delivery methods that rely on gaseous oxygen. The components of the nanoenzyme self-healing hydrogel in this invention are all natural active substances or trace elements from the body, exhibiting high biocompatibility. Furthermore, its preparation method is simple and easy to implement, with mild reaction conditions, requiring no complex equipment.
[0021] In this invention, salvianolic acid B copper cluster nanozymes are loaded onto a natural polymer self-healing hydrogel network based on catalase. The resulting hydrogel not only possesses highly efficient self-healing properties, avoiding mechanical damage during use and ensuring its service life, but its network structure also plays a crucial role as a carrier for the copper cluster nanozymes, improving the mass transfer efficiency of enzymatic reactions, enhancing catalytic stability, and extending their retention time in vivo. The natural catalase in the hydrogel components helps to synergistically catalyze oxygen supply, further improving oxygen production efficiency. The self-healing hydrogel formed based on the Schiff base interaction between carboxymethyl chitosan, catalase, and aldehyde-modified chondroitin sulfate, when used to load copper cluster nanozymes, can adapt well to wound shapes and simultaneously achieve the functions of scavenging reactive oxygen species, improving oxidative stress, and slowly releasing oxygen. Furthermore, the combined effect of salvianolic acid B copper clusters and oxygen release can promote angiogenesis, thereby achieving highly efficient repair of chronic wounds.
[0022] In this invention, based on the bioactivity of salvianolic acid B, the copper cluster nanozyme of salvianolic acid B can regulate key cells in the vascularization process, treat vascular damage, further restore blood supply, and promote the regulation of the wound microenvironment. Therefore, the nanozyme self-healing hydrogel of this invention has great application potential in the repair of tissue defects caused by hypoxia and vascular damage, such as diabetic chronic wounds. Attached Figure Description
[0023] Figure 1This invention characterizes the superoxide dismutase-like and catalase-like catalytic activities of the SalB-CuNCs (SalB-CuNCs is the SalB-CuNCs copper cluster nanozyme), wherein (a) represents the superoxide dismutase-like enzyme catalytic ability of SalB-CuNCs (SalB-CuNCs is the SalB-CuNCs copper cluster nanozyme), mainly through its catalytic activity against superoxide anion radicals (O2). ·- (a) The scavenging rate is reflected, which is concentration-dependent; (b) The catalytic activity of SalB-CuNCs catalase is mainly illustrated by measuring the increase in dissolved oxygen in 100 mmol / L H2O2 solution by different concentrations of SalB-CuNCs.
[0024] Figure 2 This invention describes the optimization of component ratios and gelation processes of nanoenzyme self-healing hydrogels in Examples 1, 2, 3, and 4. Specifically, (a) and (b) show the optimized component ratios in Examples 1 and 2, (c) and (d) show the optimized component ratios in Examples 3 and 4, and (e) and (f) show the gelation process of the nanoenzyme self-healing hydrogel in Example 4.
[0025] Figure 3 This is a scanning electron microscope image of the nanozyme self-healing hydrogel of the present invention.
[0026] Figure 4 These are images showing the self-healing effect of the nano-enzyme self-healing hydrogel of the present invention. (a) shows the self-healing effect of the hydrogel after 0 minutes; (b) shows the self-healing effect after 10 minutes; (c) shows the self-healing effect after 20 minutes; (d) shows the self-healing effect of the fragmented hydrogel after 0 minutes; (e) shows the self-healing effect of the fragmented hydrogel after 20 minutes; (f) shows a microscopic image of the self-healing effect of the hydrogel after 0 minutes; (g) shows a microscopic image of the self-healing effect of the hydrogel after 5 minutes; (h) shows a microscopic image of the self-healing effect of the hydrogel after 10 minutes; (i) shows a microscopic image of the self-healing effect of the hydrogel after 15 minutes; and (j) shows a microscopic image of the self-healing effect of the hydrogel after 20 minutes. Figure 5 This is a characterization of the intracellular catalytic oxygen supply performance of the nanoenzyme self-healing hydrogel of the present invention.
[0027] Figure 6 This invention describes the therapeutic effects of the nanoenzyme self-healing hydrogel on diabetic chronic wounds on days 0, 3, 7, 12, and 17.
[0028] Figure 7 This represents the wound healing rate. Detailed Implementation
[0029] To make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments and accompanying drawings.
[0030] This invention utilizes the bioactive polyphenolic compound salvianolic acid B as a ligand to synthesize copper cluster nanozymes in an aqueous phase, and loads them onto a self-healing hydrogel based on natural polymers to prepare a nanozyme self-healing hydrogel with catalytic oxygen supply properties for promoting the repair of chronic diabetic wounds. The salvianolic acid B polyphenolic compound, possessing antioxidant and pro-angiogenic bioactivities, is selected as the ligand, and the salvianolic acid B copper cluster nanozyme is synthesized in an aqueous phase via a one-step method. Copper nanoclusters are prone to aggregation or oxidation under physiological conditions, thus affecting their catalytic activity. In this invention, the bioactive polyphenolic molecule salvianolic acid B is selected as the ligand. On the one hand, this enhances the stability of copper nanoclusters and regulates their superoxide dismutase-like and catalase-like catalytic activities, thereby promoting in-situ oxygen supply. On the other hand, based on the pro-angiogenic activity of the small molecule ligand salvianolic acid B, the salvianolic acid B copper cluster nanozyme can regulate key cells in the vascularization process, treat vascular damage, further restore blood supply, and promote the regulation of the wound microenvironment. Based on this, copper cluster nanozymes were immobilized in a natural polymer hydrogel based on catalase. The resulting hydrogel not only has highly efficient self-healing properties, avoiding mechanical damage during use and ensuring the service life, but also, as a carrier of copper cluster nanozymes, the network structure of the hydrogel further improves catalytic stability, catalytic efficiency, and retention time in vivo, achieving a more efficient effect on promoting the repair of diabetic wounds.
[0031] This invention discloses a method for preparing a nanoenzyme self-healing hydrogel with catalytic oxygen supply properties, comprising the following steps:
[0032] 1) Preparation of copper salvianolic acid B cluster nanozyme: Using ascorbic acid as the main reducing agent and salvianolic acid B as the surface ligand and co-reducing agent, copper salvianolic acid B cluster nanozyme was prepared by a one-step reduction of copper sulfate solution in aqueous phase. Specifically, copper sulfate solution and salvianolic acid B solution were mixed and stirred at room temperature. Then, ascorbic acid was added, and the reaction was continued under heating conditions to obtain pale yellow copper salvianolic acid B nanoclusters.
[0033] The ratio of salvianolic acid B, ascorbic acid, and copper sulfate is 1-5 μmol: 100 μmol: 10 μmol. The salvianolic acid B and copper sulfate solution are mixed and stirred for 5 minutes. After adding ascorbic acid, the temperature is raised to 40-50℃, and the reaction time is 6-24 hours.
[0034] 2) Preparation of aldehyde-modified chondroitin sulfate, a hydrogel precursor: The aldehyde-modified chondroitin sulfate precursor was obtained by oxidizing chondroitin sulfate with sodium periodate. The specific process was as follows: after chondroitin sulfate was fully dissolved in water, sodium periodate solution was added under vigorous stirring, and the reaction was carried out in the dark. Finally, ethylene glycol was added to terminate the reaction, and the mixture was dialyzed using a dialysis bag and then freeze-dried.
[0035] The ratio of chondroitin sulfate to sodium periodate was 0.5 g: 0.625 mmol, the reaction time was 2 hours in the dark, and 0.5 mL of ethylene glycol was added.
[0036] 3) Preparation of nanoenzyme self-healing hydrogel: A self-healing hydrogel is formed by the Schiff base reaction between the amino groups of carboxymethyl chitosan and catalase and the aldehyde groups of aldehyde-modified chondroitin sulfate. Specifically, the copper nanoenzyme cluster of salvianolic acid B is pre-dispersed in a solution of aldehyde-modified chondroitin sulfate, and then mixed with a carboxymethyl chitosan solution and a catalase solution to form a nanoenzyme self-healing hydrogel.
[0037] The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase is 2.5-5:5:0-0.25.
[0038] The loading amount of the copper cluster nanozyme of salvianolic acid B in the nanozyme self-healing hydrogel of this invention is 1-8 mg / mL.
[0039] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0040] Example 1
[0041] 1) Preparation of Copper Tanshinone B Cluster Nanozyme: Copper Tanshinone B cluster nanozyme was prepared in aqueous phase using a one-step method with ascorbic acid as the main reducing agent and tanshinone B as the protective and co-reducing agent. Specifically, 0.1 mL of copper sulfate aqueous solution (0.1 mol / L) and 0.25 mL of tanshinone B aqueous solution (8 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the mixture was stirred at 50 °C for 24 hours to obtain pale yellow copper Tanshinone B nanoclusters. The prepared copper Tanshinone B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a molecular weight cutoff of 3 kDa, and then stored at 4 °C for later use.
[0042] 2) Preparation of aldehyde-modified chondroitin sulfate, a hydrogel precursor: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate to obtain the aldehyde-modified chondroitin sulfate hydrogel precursor. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the mixture was freeze-dried to obtain the aldehyde-modified chondroitin sulfate hydrogel precursor.
[0043] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 2.5:5:0. The loading amount of salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 2 mg / mL. Specifically, 1.2 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of a 20% wt aldehyde-modified chondroitin sulfate solution, vortexed for 30 seconds until homogeneous, to obtain a salvianolic acid B copper cluster nanoenzyme mixed with aldehyde-modified chondroitin sulfate solution. 150 μL of a 10% wt carboxymethyl chitosan solution was added to 300 μL of ultrapure water, and then mixed evenly with the salvianolic acid B copper cluster nanoenzyme mixed with aldehyde-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0044] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0045] Example 2
[0046] 1) Preparation of Copper Tanshinone B Cluster Nanozyme: Copper Tanshinone B cluster nanozyme was prepared in aqueous phase using a one-step method with ascorbic acid as the main reducing agent and tanshinone B as the protective and co-reducing agent. Specifically, 0.1 mL of copper sulfate aqueous solution (0.1 mol / L) and 0.25 mL of tanshinone B aqueous solution (8 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the mixture was stirred at 50 °C for 24 hours to obtain pale yellow copper Tanshinone B nanoclusters. The prepared copper Tanshinone B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a molecular weight cutoff of 3 kDa, and then stored at 4 °C for later use.
[0047] 2) Preparation of aldehyde-modified chondroitin sulfate precursor for hydrogel: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the product was freeze-dried.
[0048] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 2.5:5:0.25. The loading amount of salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 2 mg / mL. 1.2 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of 20% wt aldehyde-modified chondroitin sulfate solution and vortexed for 30 seconds to mix evenly. 150 μL of 10% wt carboxymethyl chitosan solution was added to 300 μL of 0.5% wt catalase solution, and then mixed evenly with the salvianolic acid B copper cluster nanoenzyme and aldehyde-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0049] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0050] Example 3
[0051] 1) Preparation of Copper Tanshinone B Cluster Nanozyme: Copper Tanshinone B cluster nanozyme was prepared in aqueous phase using a one-step method with ascorbic acid as the main reducing agent and tanshinone B as the protective and co-reducing agent. Specifically, 0.1 mL of copper sulfate aqueous solution (0.1 mol / L) and 0.25 mL of tanshinone B aqueous solution (8 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the mixture was stirred at 50 °C for 24 hours to obtain pale yellow copper Tanshinone B nanoclusters. The prepared copper Tanshinone B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a molecular weight cutoff of 3 kDa, and then stored at 4 °C for later use.
[0052] 2) Preparation of aldehyde-modified chondroitin sulfate precursor for hydrogel: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the product was freeze-dried.
[0053] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 3.75:5:0. The loading of the salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 2 mg / mL. 1.2 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of a 20% wt aldehyde-modified chondroitin sulfate solution and vortexed for 30 seconds until homogeneous. 225 μL of a 10% wt carboxymethyl chitosan solution was added to 225 μL of ultrapure water, and then mixed thoroughly with the salvianolic acid B copper cluster nanoenzyme-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0054] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0055] Example 4
[0056] 1) Preparation of Copper Tanshinone B Cluster Nanozyme: Copper Tanshinone B cluster nanozyme was prepared in aqueous phase using a one-step method with ascorbic acid as the main reducing agent and tanshinone B as the protective and co-reducing agent. Specifically, 0.1 mL of copper sulfate aqueous solution (0.1 mol / L) and 0.25 mL of tanshinone B aqueous solution (8 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the mixture was stirred at 50 °C for 24 hours to obtain pale yellow copper Tanshinone B nanoclusters. The prepared copper Tanshinone B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a molecular weight cutoff of 3 kDa, and then stored at 4 °C for later use.
[0057] 2) Preparation of aldehyde-modified chondroitin sulfate precursor for hydrogel: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the product was freeze-dried.
[0058] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 3.75:5:0.19. The loading of the salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 2 mg / mL. 1.2 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of a 20% wt aldehyde-modified chondroitin sulfate solution and vortexed for 30 seconds until homogeneous. 225 μL of a 10% wt carboxymethyl chitosan solution was added to 225 μL of a 0.5% wt catalase solution, and then mixed thoroughly with the salvianolic acid B copper cluster nanoenzyme and aldehyde-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0059] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0060] Example 5
[0061] 1) Preparation of Copper Tanshinone B Cluster Nanozyme: Copper Tanshinone B cluster nanozyme was prepared in aqueous phase using a one-step method with ascorbic acid as the main reducing agent and tanshinone B as the protective and co-reducing agent. Specifically, 0.1 mL of copper sulfate aqueous solution (0.1 mol / L) and 0.25 mL of tanshinone B aqueous solution (8 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the mixture was stirred at 50 °C for 24 hours to obtain pale yellow copper Tanshinone B nanoclusters. The prepared copper Tanshinone B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a molecular weight cutoff of 3 kDa, and then stored at 4 °C for later use.
[0062] 2) Preparation of aldehyde-modified chondroitin sulfate precursor for hydrogel: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the product was freeze-dried.
[0063] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 5:5:0.12. The loading of the salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 2 mg / mL. 1.2 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of a 20% wt aldehyde-modified chondroitin sulfate solution and vortexed for 30 seconds until homogeneous. 300 μL of a 10% wt carboxymethyl chitosan solution was added to 150 μL of a 0.5% wt catalase solution, and then mixed thoroughly with the salvianolic acid B copper cluster nanoenzyme and aldehyde-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0064] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0065] Example 6
[0066] 1) Preparation of copper salvianolic acid B cluster nanozyme: Using ascorbic acid as the main reducing agent and salvianolic acid B as a protective agent and co-reducing agent, a one-step method was used to prepare copper salvianolic acid B cluster nanozyme in aqueous phase. Specifically, copper sulfate aqueous solution (0.1 mL, 0.1 mol / L) and salvianolic acid B aqueous solution (0.25 mL, 4 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the temperature of the mixture was set at 50℃ and stirred for 24 hours to obtain pale yellow copper salvianolic acid B nanoclusters. The prepared copper salvianolic acid B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a cutoff molecular weight of 3 kDa, and then stored at 4℃ for later use.
[0067] 2) Preparation of aldehyde-modified chondroitin sulfate precursor for hydrogel: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the product was freeze-dried.
[0068] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 3.75:5:0.19. The loading of the salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 2 mg / mL. 1.2 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of a 20% wt aldehyde-modified chondroitin sulfate solution and vortexed for 30 seconds until homogeneous. 225 μL of a 10% wt carboxymethyl chitosan solution was added to 225 μL of a 0.5% wt catalase solution, and then mixed thoroughly with the salvianolic acid B copper cluster nanoenzyme and aldehyde-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0069] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0070] Example 7
[0071] 1) Preparation of copper salvianolic acid B cluster nanozyme: Using ascorbic acid as the main reducing agent and salvianolic acid B as a protective and co-reducing agent, a one-step method was employed to prepare copper salvianolic acid B cluster nanozyme in aqueous phase. Specifically, 0.1 mL of copper sulfate aqueous solution (0.1 mol / L) and 0.25 mL of salvianolic acid B aqueous solution (0.25 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the mixture was stirred at 50 °C for 24 hours to obtain pale yellow copper salvianolic acid B nanoclusters. The prepared copper salvianolic acid B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a cutoff molecular weight of 3 kDa, and then stored at 4 °C for later use.
[0072] 2) Preparation of aldehyde-modified chondroitin sulfate precursor for hydrogel: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the product was freeze-dried.
[0073] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 3.75:5:0.19. The loading of the salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 2 mg / mL. 1.2 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of a 20% wt aldehyde-modified chondroitin sulfate solution and vortexed for 30 seconds until homogeneous. 225 μL of a 10% wt carboxymethyl chitosan solution was added to 225 μL of a 0.5% wt catalase solution, and then mixed thoroughly with the salvianolic acid B copper cluster nanoenzyme and aldehyde-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0074] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0075] Example 8
[0076] 1) Preparation of Copper Tanshinone B Cluster Nanozyme: Copper Tanshinone B cluster nanozyme was prepared in aqueous phase using a one-step method with ascorbic acid as the main reducing agent and tanshinone B as the protective and co-reducing agent. Specifically, 0.1 mL of copper sulfate aqueous solution (0.1 mol / L) and 0.25 mL of tanshinone B aqueous solution (8 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the mixture was stirred at 50 °C for 24 hours to obtain pale yellow copper Tanshinone B nanoclusters. The prepared copper Tanshinone B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a molecular weight cutoff of 3 kDa, and then stored at 4 °C for later use.
[0077] 2) Preparation of aldehyde-modified chondroitin sulfate precursor for hydrogel: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the product was freeze-dried.
[0078] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 3.75:5:0.19. The loading of the salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 1 mg / mL. 0.6 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of a 20% wt aldehyde-modified chondroitin sulfate solution and vortexed for 30 seconds until homogeneous. 225 μL of a 10% wt carboxymethyl chitosan solution was added to 225 μL of a 0.5% wt catalase solution, and then mixed thoroughly with the salvianolic acid B copper cluster nanoenzyme-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0079] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0080] Example 9
[0081] 1) Preparation of Copper Tanshinone B Cluster Nanozyme: Copper Tanshinone B cluster nanozyme was prepared in aqueous phase using a one-step method with ascorbic acid as the main reducing agent and tanshinone B as the protective and co-reducing agent. Specifically, 0.1 mL of copper sulfate aqueous solution (0.1 mol / L) and 0.25 mL of tanshinone B aqueous solution (8 mmol / L) were added to 10 mL of ultrapure water, and the mixture was stirred at room temperature for 5 minutes. Then, ascorbic acid (0.1 mL, 1 mol / L) was added, and the mixture was stirred at 50 °C for 24 hours to obtain pale yellow copper Tanshinone B nanoclusters. The prepared copper Tanshinone B nanoclusters were purified by ultrafiltration centrifugation using ultrafiltration centrifuge tubes with a molecular weight cutoff of 3 kDa, and then stored at 4 °C for later use.
[0082] 2) Preparation of aldehyde-modified chondroitin sulfate precursor for hydrogel: Chondroitin sulfate (molecular weight 5-10 kD) was aldehyde-modified using sodium periodate. Specific preparation steps are detailed in: Li, H.; Cheng, F.; Wei, X.; Yi, X.; Tang, S.; Wang, Z.; Zhang, YS; He, J.; Huang, Y., Mater. Sci. Eng. C 2021, 118, 111324. The experimental steps are as follows: 0.5 g of chondroitin sulfate was dissolved in 50 mL of ultrapure water. 2.5 mL of sodium periodate (0.25 mol / L) was added under vigorous stirring, and the reaction was carried out in the dark for 2 hours. Then, 0.5 mL of ethylene glycol was added to terminate the reaction. After dialyzing using a dialysis bag for 4 days, the product was freeze-dried.
[0083] 3) Preparation of the nanoenzyme self-healing hydrogel: The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase was 3.75:5:0.19. The loading amount of salvianolic acid B copper cluster nanoenzyme in this nanoenzyme self-healing hydrogel was 4 mg / mL. 2.4 mg of salvianolic acid B copper cluster nanoenzyme was pre-dispersed in 150 μL of a 20% wt aldehyde-modified chondroitin sulfate solution and vortexed for 30 seconds until homogeneous. 225 μL of a 10% wt carboxymethyl chitosan solution was added to 225 μL of a 0.5% wt catalase solution, and then mixed thoroughly with the salvianolic acid B copper cluster nanoenzyme and aldehyde-modified chondroitin sulfate solution to form the nanoenzyme self-healing hydrogel.
[0084] 4) Biomedical Applications: Nanozyme self-healing hydrogels and human umbilical vein endothelial cells (HUVECs) were co-cultured under hypoxic conditions to investigate the catalytic oxygen supply performance of the hydrogels on the endothelial cells. Furthermore, the nanozyme hydrogels were applied to the wounds of streptozotocin-induced diabetic mice to explore the hydrogels' efficacy in promoting the repair of chronic diabetic wounds.
[0085] Example 10
[0086] Same as Example 1, except that in step 1), the temperature of the mixture solution is set to 40°C and stirred for 24 hours.
[0087] Example 11
[0088] Same as Example 1, except that in step 3), the temperature of the mixture solution is set to 50°C and stirred for 6 hours.
[0089] Example 12
[0090] Same as Example 1, except that in step 3), the temperature of the mixture solution is set to 45°C and stirred for 12 hours.
[0091] Example 13
[0092] Same as Example 1, except that in step 3), the mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate and catalase is 2.5:5:0.1.
[0093] Example 14
[0094] Same as Example 1, except that in step 3), the mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate and catalase is 3:5:0.25.
[0095] Example 15
[0096] Same as Example 1, except that in step 3), the mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate and catalase is 5:5:0.2.
[0097] Example 16
[0098] Same as Example 1, except that in step 3), the mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate and catalase is 4:5:0.05.
[0099] Example 17
[0100] Same as Example 1, except that in step 3), the loading amount of the copper cluster nanozyme of salvianolic acid B in the self-healing hydrogel of the nanozyme is 8 mg / mL.
[0101] Comparative Example 1
[0102] Similar to Example 4, except that in step 3), copper cluster nanozyme of salvianolic acid B was not added, and a self-healing hydrogel was prepared.
[0103] Comparative Example 2
[0104] Similar to Example 1, but different in that, in step 1), the temperature of the mixture solution was set to 37°C, which made it impossible to prepare the copper cluster nanozyme of salvianolic acid B.
[0105] Comparative Example 3
[0106] Similar to Example 1, but different in that, in step 1), if the stirring time is not within 6-24 hours, it is impossible to prepare the copper cluster nanozyme of salvianolic acid B.
[0107] As can be seen from Comparative Examples 2 and 3, the preparation of the salvianolic acid B copper cluster nanozyme in the nanozyme self-healing hydrogel of the present invention must adopt the temperature and time specified in the present invention.
[0108] The copper cluster of salvianolic acid B prepared by this invention has excellent enzyme-like catalytic activity. Figure 1 This section characterizes the superoxide dismutase-like and catalase-like catalytic activities of the salvianolic acid B copper cluster nanozyme prepared in Example 1. The superoxide dismutase-like catalytic activity of the salvianolic acid B copper cluster nanozyme was determined by characterizing its ability to inhibit superoxide anion free radicals. Specifically, xanthine / xanthine oxidase generates superoxide anion free radicals, and nitroblue tetrazolium chloride (NBT) is used as a colorimetric probe. Figure 1 As shown in (a), the scavenging efficiency of superoxide anion increased with increasing concentration of salvianolic acid B copper clusters, indicating higher superoxide dismutase-like activity. The inhibition rate of superoxide anion by 40 μg / mL salvianolic acid B copper clusters was 50%. The catalase-like catalytic activity of salvianolic acid B copper clusters was determined by measuring the dissolved oxygen production in hydrogen peroxide (100 mmol / L, pH = 7.4) solution using a portable dissolved oxygen meter. Figure 1 As shown in (b), the dissolved oxygen concentration of the 25 μg / mL salvianolic acid B copper cluster solution increased significantly by 6 mg / L after the addition of hydrogen peroxide solution for 10 minutes, indicating that the salvianolic acid B copper cluster has good catalase-like catalytic activity, and this increase in dissolved oxygen is dose-dependent.
[0109] Figure 2 This invention relates to the optimization of the component ratios and gelation process of the nanozyme self-healing hydrogel. Figure 2 (a), (b), (c) and (d) in the examples are the hydrogels prepared in Examples 1, 2, 3 and 4, respectively. Figure 2 Images (e) and (f) show the gelation process of the nanozyme self-healing hydrogel prepared in Example 4. In the synthesis of the hydrogel, besides the Schiff base reaction between the amino group of carboxymethyl chitosan and the aldehyde group of aldehyde-modified chondroitin sulfate, the amino group on the natural catalase also plays a crucial role in promoting the gelation of the hydrogel. By optimizing the concentration, it was found that... Figure 2In (a) and (b), neither catalase nor other enzymes could form a good hydrogel. Further increasing the carboxymethyl chitosan content did not result in the formation of a hydrogel structure. Figure 2 (c) However, after the addition of catalase, it is converted into a hydrogel state under the action of amino groups on the surface of catalase. Figure 2 (d) Therefore, the final optimized mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase is 3.75:5:0.19 as in Example 4. Figure 2 As shown in (e), carboxymethyl chitosan and catalase solution are in solution state. After adding aldehyde-modified chondroitin sulfate mixed with copper cluster nanoenzyme of salvianolic acid B, as shown in (e), Figure 2 As shown in (f), the solution gradually gels to obtain a nanoenzyme self-healing hydrogel (COC@SalB-Cu).
[0110] Figure 3 This is a scanning electron microscope (SEM) image of the nanozyme self-healing hydrogel of the present invention. The morphology of the nanozyme self-healing hydrogel prepared in Example 4 was characterized. The prepared hydrogel was rapidly frozen in liquid nitrogen and then freeze-dried in a freeze dryer. The freeze-dried hydrogel was then adhered to a conductive adhesive and vacuum-sputtered with gold. The surface morphology of the hydrogel was observed using a scanning electron microscope. Figure 3 It can be seen that the nanoenzyme hydrogel has a porous structure with uniform pore size.
[0111] Figure 4 Figures (a)-(j) show the self-healing effect of the nanoenzyme self-healing hydrogel of this invention. Figure 4 The self-healing hydrogel of the nanozyme obtained in Example 4 was studied by gently attaching two or small segments of the hydrogel. For example... Figure 4 As shown, the hydrogels were observed to heal spontaneously within 20 minutes, and in particular, microscopic observation revealed that the gap between the two hydrogels gradually disappeared over time. The rapid self-healing performance of the nanoenzyme self-healing hydrogel in this invention is attributed to the dynamic and reversible covalent Schiff base network formed between the aldehyde groups in aldehyde-modified chondroitin sulfate and the amino groups in carboxymethyl chitosan or catalase.
[0112] Figure 5 This is a characterization of the intracellular oxygen supply performance of the nanoenzyme self-healing hydrogel of the present invention. Figure 5 The COC and COC@SalB-Cu hydrogels in the examples are the self-healing hydrogel and nanozyme self-healing hydrogel obtained in Comparative Example 1 and Example 4, respectively. The catalytic oxygen supply capacity of the hydrogels in HUVECs cells was determined using the oxygen-sensitive fluorescent probe Ru(dpp)3Cl2. HUVECs were seeded in 8-well plates at a density of 2 × 10⁶. 4Cells / wells were incubated under hypoxic conditions for 18 hours. Hypoxic chambers were used to simulate the hypoxic environment of cell culture, providing 1% oxygen, 5% carbon dioxide, and 95% nitrogen. Self-healing hydrogel, copper tanshinone B cluster nanozyme, and nanozyme self-healing hydrogel with H2O2 (100 μM) were co-incubated with HUVECs for 12 hours. Cells were washed with DPBS and then cultured again under hypoxic conditions for 4 hours with a Ru(dpp)3Cl2 oxygen-sensitive fluorescent probe (0.5 μM). The relative fluorescence intensity of the fluorescent probe (λex = 488 nm) was measured using fluorescence confocal microscopy to reflect intracellular O2 levels. Figure 5 It was found that the control group and the H2O2-only treatment group showed obvious fluorescence signals, indicating low oxygen content. In contrast, the fluorescence intensity of the self-healing hydrogel group and the salvianolic acid B copper cluster nanozyme group decreased, and the nanozyme self-healing hydrogel treatment group showed the lowest fluorescence signal, indicating that the nanozyme self-healing hydrogel in this invention has good intracellular catalytic oxygen supply performance.
[0113] Figure 6 and Figure 7 This refers to the therapeutic effect of nanozyme self-healing hydrogel on chronic diabetic wounds; among them, Figure 6 Images of the wound on days 0, 3, 7, 12, and 17; Figure 7 The wound healing rate is indicated. A diabetic mouse model was established using streptozotocin. Mice were fed a high-fat, high-sugar diet to maintain a diabetic state for wound healing experiments. After anesthesia and hair removal, two full-thickness skin wounds with a diameter of 7 mm were made on the back of each mouse using small surgical scissors. The mice were then randomly divided into four groups: a) control group (no treatment); b) Tegaderm™ (3M) group (3M commercial dressing applied to the wound); c) COC hydrogel group (self-healing hydrogel obtained in Comparative Example 1 applied to the wound); and d) COC@SalB-Cu hydrogel group (nanozyme self-healing hydrogel obtained in Example 4 applied to the wound). The wounds were photographed at 3, 7, 12, and 17 days after treatment, and the wound size and healing rate were calculated using ImageJ software. Figure 6 and Figure 7The results showed that the COC@SalB-Cu nanoenzyme self-healing hydrogel treatment group exhibited better wound healing effects compared to the other three groups. On day 3, the wound healing rate of the COC@SalB-Cu hydrogel treatment group (37.5%) was significantly higher than that of the control group (11.1%), the 3M group (5.8%), and the COC hydrogel group (14.5%). On day 7, the wound healing rate of the COC@SalB-Cu hydrogel treatment group rapidly increased to 76.2%, reaching 95.2% by day 12. On day 17, the wounds in the COC@SalB-Cu hydrogel treatment group were completely closed and covered with regenerated hair, while the wounds in the other groups remained unhealed. Notably, during the 17-day treatment period, the wound size in the COC hydrogel group was significantly smaller than that in the control and 3M groups, indicating that the hydrogel alone promotes wound healing in diabetic patients by catalyzing the decomposition of hydrogen peroxide through catalase, thereby supplying oxygen. Meanwhile, the COC@SalB-Cu hydrogel treatment group exhibited the best wound healing performance, likely due to the combined effects of the nanozyme cascade catalysis enhancing its oxygen supply and the nanozyme's role in promoting vascular remodeling. In summary, the oxygen-supplying nanozyme self-healing hydrogel prepared in Example 4 demonstrates excellent efficacy in promoting the repair of chronic diabetic wounds.
[0114] This invention synthesizes salvianolic acid B copper cluster nanozymes in an aqueous phase using a polyphenolic compound, salvianolic acid B, as a ligand in a one-step process. Furthermore, the salvianolic acid B copper cluster nanozyme is loaded into a natural polymer self-healing hydrogel network based on catalase. The natural catalase in the hydrogel component helps to synergistically catalyze oxygen supply, further improving oxygen production efficiency. Using salvianolic acid B as a ligand not only enhances the stability of the copper clusters and regulates their enzyme-like catalytic oxygen production performance, but it is also key to regulating vascular endothelial cells during tissue repair, further restoring blood supply and promoting oxygen delivery.
[0115] This invention differs from traditional oxygen supply strategies that rely on gaseous oxygen. It utilizes in-situ cascade catalysis to convert excess reactive oxygen species into hydrogen peroxide, which then catalyzes the production of dissolved oxygen. This effectively avoids the limitations of traditional oxygen delivery methods, such as limited tissue penetration and short duration of action. The nanoenzyme self-healing hydrogel in this invention is composed entirely of natural active substances or trace elements found in vivo, exhibiting high biocompatibility. Furthermore, its preparation method is simple and easy to implement, with mild reaction conditions requiring no complex equipment. The self-healing hydrogel co-crosslinked with carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase, when used to load salvianolic acid B copper cluster nanoenzymes, can adapt well to wound shapes and simultaneously scavenge reactive oxygen species, improve oxidative stress, and slowly release oxygen. In addition, the combined effect of salvianolic acid B copper clusters and oxygen release can promote angiogenesis, further restoring blood supply and promoting wound microenvironment regulation. The nanoenzyme self-healing hydrogel of this invention has significant application potential in repairing tissue defects caused by hypoxia and vascular injury, such as in diabetic chronic wounds.
[0116] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A method for preparing a nanoenzyme self-healing hydrogel with catalytic oxygen supply properties, characterized in that, Includes the following steps: 1) Using ascorbic acid as the main reducing agent and salvianolic acid B as the surface ligand and co-reducing agent, copper cluster nanozyme of salvianolic acid B was prepared by reducing copper sulfate solution in aqueous phase in one step. 2) Copper cluster nanozymes of salvianolic acid B were loaded into a self-healing hydrogel co-crosslinked with carboxymethyl chitosan, aldehyde-modified chondroitin sulfate and catalase to obtain a nanozyme self-healing hydrogel with catalytic oxygen supply properties. The heating temperature is 40-50 ℃, and the time is 6-24 hours; The ratio of salvianolic acid B, ascorbic acid to copper sulfate is 1-5 μmol: 100 μmol: 10 μmol; The mass ratio of carboxymethyl chitosan, aldehyde-modified chondroitin sulfate, and catalase is 2.5-5:5:0-0.25; The loading capacity of the copper cluster nanozyme of salvianolic acid B in the nanozyme self-healing hydrogel with catalytic oxygen supply properties is 1-8 mg / mL.
2. The method for preparing the nanoenzyme self-healing hydrogel with catalytic oxygen supply properties according to claim 1, characterized in that, Step 1) The specific process is as follows: After mixing copper sulfate solution and salvianolic acid B solution and stirring evenly, ascorbic acid is added, and the reaction is carried out under heating to obtain copper salvianolic acid B nanoclusters.
3. The method for preparing the nanoenzyme self-healing hydrogel with catalytic oxygen supply properties according to claim 1, characterized in that, In step 2), the amino group of carboxymethyl chitosan or the amino group of catalase reacts with the aldehyde group of aldehyde-modified chondroitin sulfate to form a Schiff base reaction, thereby forming a self-healing hydrogel.
4. The method for preparing the nanoenzyme self-healing hydrogel with catalytic oxygen supply properties according to claim 1, characterized in that, Step 2) involves dispersing the copper cluster nanozyme of salvianolic acid B in an aldehyde-modified chondroitin sulfate solution, then mixing it with a carboxymethyl chitosan solution and a catalase solution to form a nanozyme self-healing hydrogel with catalytic oxygen supply properties.
5. A nanoenzyme self-healing hydrogel with catalytic oxygen supply properties prepared by the method according to any one of claims 1-4.
6. The application of a nanoenzyme self-healing hydrogel with catalytic oxygen supply properties prepared by the method according to any one of claims 1-4 in the repair of diabetic wounds.
Citation Information
Patent Citations
Composition and method for biofouling inhibition of membrane separation device
CA2929494A1
Hydrophilic polymeric coatings for medical articles with visualization moiety
US20130261566A1